Poor vitamin D status, obesity and associated health outcomes: focus on groups at risk - Hirani, Vasant (2011)
Vitamin D deficiency affects many population groups; but there are some groups that are at increased risk such as older people. It has been shown that obesity may influence vitamin D status. There is also emerging evidence linking poor vitamin D status to obesity related chronic diseases. This collation of original published work submitted in this thesis includes studies focusing on older people and deprived groups in areas of current public health concern and presents the prevalence and trends in vitamin D status among older people, examines the influence of poor vitamin D status with deprivation, obesity and other health outcomes such as depression. It also examines prevalence and trends in overweight and obesity and associated risk factors among older people. Particular issues that have been identified in this collation of research are that older people, especially those living in institutions are at a high risk of vitamin D deficiency and that there have been no improvements in vitamin D status among older people living in the community since 1994. The research also shows that poor vitamin D status is associated with obesity among older people living in the community, and prevalence of obesity is increasing among this group. Poor vitamin D status is associated with many risk factors including season, ethnicity, poor health status and depression in older people. It has also been identified that the low income/deprived population is another group at high risk of poor vitamin D status and findings from this study show inverse associations between 25(OH)D levels and body mass index. Overall the thesis shows that there are population groups at high risk of vitamin D deficiency and obesity. Both of these areas are of public health concern that can impact health outcomes. There is some potential to address and improve the situation through public health policies such as appropriate vitamin D supplementation and food fortification, interventions for the prevention and management of overweight and obesity, and optimising the management of chronic diseases. Policies that include strategies to prevent and address these areas of concern have the potential to improve the quality of life, reduce morbidity and mortality, can be cost effective for the health service and can have an impact particularly on groups at risk.